Risk factors associated with severe and recurrent angioedema: An epidemic linked to ACE‐inhibitors. (17th June 2014) - Loftus, Patricia A.; Tan, Melin; Patel, Gunj; Lin, Juan; Helman, Sam; Badhey, Arvind; Du, Eugenie; Smith, Richard V.; Fried, Marvin P.; Ow, Thomas J.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To evaluate the etiology and risk factors for severe manifestation and recurrent episodes of angioedema; to evaluate efficacy of short‐term and long‐term management strategies for angioedema among a high‐risk population. Study Design Institutional review board‐approved retrospective review of a large, urban population. Methods Data from 875 adult patients treated from January 2008 to December 2013 with the diagnosis of angioedema were obtained using the Clinical Looking Glass utility and review of medical records. Demographic and clinicopathologic risk factors were recorded. The major outcomes evaluated were hospital admission, need for airway intervention, and recurrent episodes of angioedema following the first presentation. Initial treatment strategy and follow‐up recommendations were also recorded. Results The most common cause of angioedema was angiotensin converting enzyme inhibitor (ACEi)‐induced (496 [56.6%]). Significant risk factors for severe cases of angioedema included older age, Hispanic race, ACEi‐induced angioedema type, American Society of Anesthesiologists class III or above, coexistent cardiopulmonary disease, and a positive smoking history. A total of 17.2% of patients experienced recurrent attacks of angioedema; of those patients, 25.9% were still taking an ACEi at subsequent presentation. Risk factors for recurrent episodes included older age, idiopathic angioedema type, and coexistent cardiopulmonary disease. Only 54.1% of patients who experienced ACEi‐induced angioedema had electronic medical record documentation of these allergies. Conclusions Knowledge of risk factors for severe and recurrent episodes of angioedema and improved education for both healthcare providers and patients, specifically related to ACEi use and allergy documentation, may significantly decrease the burden and morbidity of angioedema among high risk populations. Level of Evidence 2b. Laryngoscope, 124:2502–2507, 2014